Metal concentration and environmental risk assessment of roadside soils in highly urbanized areas of Bukidnon, Philippines - JOHN REY NATINGA LABAJO; JUNESA UDTOJAN CRISTOBAL; MYRNA GEMENTIZA PABIONA; ROMIL S. TAN; JESSIE GUTIERREZ-SUSON; LYDIA EBARE-TIONGCO (Nusantara Bioscience, 2025)
Abstract. Labajo JRN, Cristobal JU, Pabiona MG, Tan RS, Gutierrez-Suson J, Ebare-Tiongco L. 2025. Metal concentration and environmental risk assessment of roadside soils in highly urbanized areas of Bukidnon, Philippines. Nusantara Bioscience 17: 68-83. Five urbanized localities in Bukidnon were selected based on population density and vehicular activities. Soil samples were collected, and metal concentration was determined using AAS, sediment quality guidelines, and the contamination index. The study assessed the metal concentration and environmental risk assessment of soil along the road from five localities in the Province of Bukidnon: It was observed that the highest total concentration for Mn (229.46±21.26), Fe (199.87±51.78), Co (38.13±16.18), Zn (32.43±19.13), Cu (18.17±4.52), Cr (17.95±1.76), and Cd (0.901±0.063) mg kg-1 respectively, Mn, exhibited the highest (lgeo), of "moderately contaminated" level. Co was the highest CF value corresponding to "moderate contamination." The Pollution Load Index (PLI) value of all sampling sites was "perfection or low pollution index." Mn has the highest EFs of "moderately severe enrichment." The Potential Ecological Risk Index (PERI) revealed that metals are "low risk" and "low." For a multi-element factor, there is "no potential ecological risk" for all study sites. The Toxic Risk Index (TRI) shows "no toxic risk" observed by the metal(iod)s. While Cr has the highest mHQ, with "low severity of contamination." The study underscores the need for practical measures to mitigate metal contamination in agricultural areas, recommending that policymakers, local government officials, and stakeholders develop mitigation approaches to protect the environment and public health.